The Effect of Career Development on Employee Performance (Case Study at CV Anggara Prima) - Aspizain Caniago; Agung Edi Rustanto (Majalah Ilmiah Bijak, 2022)
This research is motivated by the phenomenon of a decrease in the level of work productivity in Indonesia which has an impact on employee performance. One of the efforts made by the company in order to increase employee productivity and performance is through employee career development through training activities. Through employee career development, employee knowledge, abilities and skills will increase and will have an impact on employee productivity and performance. This study aims to determine the effect of career development on employee performance. Population is the total number of objects of a study. The population in this study were employees of PT Anggara Prima, totaling 99 people. While the sample in this study were 80 people. Data analysis technique using simple linear regression analysis. The results showed that there was a positive influence between career development on employee performance when viewed from the t-test with a t-count value (7.185 > 1.988) with a significant level of 0.05. Based on the analysis of the coefficient of determination, it can be seen that the R Square value of 0.398 or 39.8% of employee performance variables can be explained by career development variables while the remaining 60.2% is influenced by other variables not explained by the author in this study.product quality) to the dependent variable (purchase interest) is 58.9%